Nahḍat al-‘Ulamā’ bay al-Bātinīyah al-Jāwīyah wa al-Taṣawwuf al-Islāmī: ‘Arḍun wa Munāqashāt - Nursamad, Muhammad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
Three kebatinan